Breast reconstruction in a patient with an implanted deep brain stimulator - Yukiyo Tsunekawa; Hideyoshi Sato; Chisato Koyama; Yuichi Oka; Kazuhiro Toriyama (JPRAS Open, 2020)
Summary: Deep brain stimulators (DBSs) are sometimes used to treat refractory movement disorders such as Parkinson's disease. When DBSs are implanted in a subcutaneous pocket in the chest region, breast reconstruction becomes a challenge because monopolar electrocautery can lead to DBS dysfunction or brain tissue damage caused by heat. We report a patient with a DBS who underwent one-stage implant-based breast reconstruction. We switched off the DBS before surgery and used monopolar electromagnetic cautery with minimum power settings to undermine the subcutaneous pocket for the breast implant. The DBS was switched back on immediately after completion of the surgery. The patient's postoperative recovery was uneventful with the DBS fully functional.